Cowling Price Theorem for Low Dimensional Nilpotent Lie Groups - Bhatta, C. R. (Tribhuvan University Journal, 2010)
We extend an uncertainty principle due to Cowling and Price to low dimensional Nilpotent Lie groups G4. The uncertainty principle is age neralization of a classical result due to Hardy.